The Palgrave Handbook of Development Cooperation for Achieving the 2030 Agenda Contested Collaboration - Chaturvedi, Sachin (Springer Nature, 2021)
This open access handbook analyses the role of development cooperation in achieving the 2030 Agenda in a global context of 'contested cooperation'. Development actors, including governments providing aid or South-South Cooperation, developing countries, and non-governmental actors (civil society, philanthropy, and businesses) constantly challenge underlying narratives and norms of development. The book explores how reconciling these differences fosters achievement of the Sustainable Development Goals.